PENGARUH PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN 212 MART CONDET BATU AMPAR - Fahra Destarini; Bono Prambudi (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2020)
The Minimarket 212 Mart Condet has become an interesting object for researchers because this new minimarket has emerged against the background of the actions of defending Muslims for blasphemy (Q.S. Al-Maidah: 51). This study aims to analyze the effect of Products and Prices on Purchasing Decisions on Minimarket 212 Mart Condet consumers. The data used in this study are primary data obtained from the questionnaire. The data processing method used by researchers is multiple linear regression analysis. This study uses the SPSS computer program version 22.0. The results showed that the product has a positive and significant influence, which means that if the product is increasingly positive or good or good, the stronger the purchasing decision. The results of the research Price has a negative and not significant influence on purchasing decisions, which means that if negative means different directions the higher the price or the higher the purchase decision decreases.